Chemical rescue of H+ delivery in proton transfer mutants of reaction center of photosynthetic bacteria - Maróti Péter (2019)
In the native and most mutant reaction centers of bacterial photosynthesis, the electron transfer is coupled to proton transfer and is rate limiting for the second reduction of Q(B)(-) -> Q(B)H(2). In the presence of divalent metal ions (e.g. Cd2+) or in some ("proton transfer") mutants (L210DN/M17DN or L213DN), the proton delivery to Q(B)(-) is made rate limiting and the properties of the proton pathway can be directly examined. We found that small weak acids and buffers in large concentrations (up to 1 M) were able to rescue the severely impaired proton transfer capability differently depending on the location of the defects: lesions at the protein surface (proton gate H126H/H128H + Cd2+), beneath the surface (M17DN + Cd2+, L210DN/M17DN) or deep inside the protein (L213DN) could be completely, partially or to very small extent recovered, respectively. Small zwitterionic acids (azide/hydrazoic acid) and buffers (tricine) proved to be highly effective rescuers consistent with their enhanced binding affinity and access to any of the proton acceptors (including Q(B)(-) itself) in the pathway. As a consequence, back titration of the protons at L212Glu could be observed as a pH-dependence of the rate constant of the charge recombination in the presence of azide or formate. Model calculations support the collective influence of the acid cluster on the change of the protonation states upon extension of the cluster with the bound small acid. In proton transfer mutants, the rescuing agents decreased the free energy of activation together with their enthalpic and entropic components. This is in agreement with the hypothesis that they function as protein-penetrating protonophores delivering protons into the chain and select dominating paths out of many alternate routes. We estimate that the proton delivery will be accelerated in one pathway out of 100-200 alternate pathways. The implications for design of the chemical recovery of impaired intra-protein proton transfer pathways in proton transfer mutants are discussed.
Keywords: Biológiai tudományok; Egészségtudományok